2012
DOI: 10.1007/s00580-012-1671-7
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus frequency among Iraqi thyroid disorder patients

Abstract: Micronucleus (MN) assay has been extensively used in detection of DNA damage, instability in cancer, and genetic disorders. In the current study, MN, binucleated cells, and nuclear division index (NDI) were investigated in Iraqi patients with thyroid disorders. The results indicated significantly (p < 0.05) increased binucleated cells with micronucleus (BNMN) frequencies in thyroid cancer group (37.58 ± 3.07) versus other thyroid disorder groups (6.60 ± 1.29, 14.90 ± 1.69, 15.56 ± 1.76). On the other hand, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…However, there are many studies on genomic damage in different cancer types. The result on the MN frequency obtained in the present study is consistent with the results of other studies 8,[12][13][14][15] . There are only a few studies evaluating the frequency of NPB, NBUD and MN 21 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, there are many studies on genomic damage in different cancer types. The result on the MN frequency obtained in the present study is consistent with the results of other studies 8,[12][13][14][15] . There are only a few studies evaluating the frequency of NPB, NBUD and MN 21 .…”
Section: Discussionsupporting
confidence: 93%
“…These nuclear anomalies, which are markers of genomic instability, are frequently seen in cancer 6 . Numerous studies have validated that there is a positive correlation between increased MN, NPB and NBUD frequencies in PBL and cancer risk 6,8,[12][13][14][15] . The CBMN assay is a useful method to monitor genomic instability, and many recent events reveal that the increased genomic instability in PBL might be an early event in carcinogenesis 6,16 .…”
Section: Introductionmentioning
confidence: 98%
“…In this study the authors confirmed that two men in the exposed group, who have hypothyroidism (receive a therapy with euthyrox), have increased number of MNi (Table 2). In the research of AL FAISAL et al (2012), there was an evidence of increased MN frequencies in patients with thyroid disorder, compared to healthy population. So many factors like age, gender, smoking etc.…”
Section: Table 2 General Characteristics Mni Frequency and Mn Distrib...mentioning
confidence: 95%
“…The inadequate thyroid hormones availability due to defect of synthesis of these hormones, the majority of these defects are due to mutations in thyroglobulin-TG and thyroid peroxidase-TPO genes [12]. Mutations among TPO and TG genes associated with thyroid disorders were strongly proved [13,14,15]. The current study is attempted to find the TPO mutations associated with PCOS combined with thyroid hormones disturbances.…”
Section: Introductionmentioning
confidence: 96%